PERCENTAGE OF A NUMBER AND ITS CALCULATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The concept of percentage is an integral part of mathematics and daily life, providing a standard way to represent proportions and comparisons. A percentage is defined as a fraction of 100, which makes it easier to understand and compare quantities across various fields. This article explores the definition, history, methods of calculation, applications, and common errors related to percentages. It emphasizes the importance of percentage in mathematics, education, business, science, and everyday problem-solving. By offering theoretical explanations and practical examples, the paper highlights how percentages simplify complex comparisons, making them universally applicable and easy to interpret.